EVALUASI SANITASI BERBASIS MASYARAKAT BERDASARKAN PILAR PERTAMA STOP DEFAKASI DISEMBARANG TEMPAT DI SOMODARAN, BANYURADEN, GAMPING, SLEMAN - Asyifa Adwibaraski; Sigid Sudaryanto; Naris Dyah Prasetyawati (Jurnal Teknologi Kesehatan (Journal of Health Technology), 2019)
The government attempted to address the issue of sanitation, especially Clean and Healthy Behavior and healthy latrine ownership with the efforts is the National Strategy community-led total sanitation (CLTS) which is expected to prevent or minimize the morbidity and mortality. The purpose of this study to assess the success of the triggers of Community-Led Total Sanitation (CLTS) First Pillar in Somodaran Village, Banyuraden, Gamping, Sleman 2019. The research method with the type and design of a study conducted using a qualitative approach to the type of research and survey methods cross observational sectional descriptive. The population in this study were residents in the Somodaran Village, Banyuraden, Gamping, Sleman, Yogyakarta, which has been following CLTS triggering the First Pillar of 50 respondents using Total Sampling. According to the research level of success on the First Pillar of CLTS triggered open defecation free in getting in this study before and after triggering an increase of behaviour change. Where prior to the detonation there are 56% who still behave open defecation free but after the detonation to 80% of respondents has changed the behaviour with no defecation Gratuitous. Availability latrines of 50 respondents prior to detonation only 30% availability of latrines increased 10%, subsequent to the triggering ie to 40% already have private latrines in every home and the condition of the respondents latrines in every home prior to the detonation of 86.7% and after the detonation of 90% , The conclusion of this study an increase though not so many before and after triggering the respondents.